Conceptual development of an ergonomic passenger seat and cabin design for single aisle transport airship - Aminian, Negin Ozve (2019)
Recently, there have been progressive interests in having airships as alternative mass passenger air transportation means. Many research studies have been conducted so far on the external shape and structural design of passenger transport airships; however, there is little emphasis placed on the internal passenger cabin designs. This is despite the fact that passenger comfort is widely acknowledged as one of the main criteria to attract passengers for the flying services. Current passenger cabin designs that have been operated or envisioned for passenger transport airships are either too luxurious or too compact, which are not suitable to be used onboard a mass passenger transport airship with anticipated similar capacity to a commercial transport aircraft. Therefore, there exists a clear design gap that becomes the driving motivation to be addressed by this study. Subsequently, the research objectives are to establish cabin design factors that contribute to the improvement of passengers’ comfort level, conceptually develop an ergonomic passenger seat design that could provide an adequate comfort level for passengers of a mass passenger transport airship and conceptually develop optimal passenger cabin for mass passenger transport airships using fuzzy logic method.